1985
DOI: 10.1002/dc.2840010209
|View full text |Cite
|
Sign up to set email alerts
|

Improved antigen detection in ethanol‐fixed cytologic specimens. A modified avidin‐biotin‐peroxidase complex (ABC) method

Abstract: A new amplification technique is described for the detection of small amounts of antigen in ethanol-fixed cytologic specimens and formalin-fixed tissues. By adding a third antibody layer to the already sensitive avidin-biotin immunoperoxidase system, we have demonstrated a considerable increase in both the quantitative and qualitative aspects of this immunostaining method. In evaluating this technique, we employed a previously defined small cell lung carcinoma cell surface antigen system and monoclonal antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…As for the ABC system, Gupta et al, 1985) employed a third biotin-conjugated antibody, directed against the secondary biotin-conjugated antibody, thus increasing the total number of biotin molecules on the antigen and consequentially the number of ABC complexes bound. However, this method may have some disadvantages since no further amplification is possible due to the limited availability of species specific anti-immunoglobulin reagents.…”
Section: Discussionmentioning
confidence: 99%
“…As for the ABC system, Gupta et al, 1985) employed a third biotin-conjugated antibody, directed against the secondary biotin-conjugated antibody, thus increasing the total number of biotin molecules on the antigen and consequentially the number of ABC complexes bound. However, this method may have some disadvantages since no further amplification is possible due to the limited availability of species specific anti-immunoglobulin reagents.…”
Section: Discussionmentioning
confidence: 99%
“…The Division of Cytopathology and Cytometry at the University of Pennsylvania is responsible for preparing, immunostaining, and interpreting a minimum of four slides (two for each antibody) from each patient's combined induced and postinduction specimens plus positive and negative control slides using the doublebridge ABC method of Gupta et al 26 Immunostained slides are received back at the Frost Center where they undergo optical/ electronic quantitation.27'28 Interpretations of Papanicolaoustained slides, immunostained slides, and optical/electronic quantitation are entered onto the database maintained by the Coordinating Center at Johns Hopkins Oncology Biostatistics. Finally, the Frost Center Laboratory stores all slides and prepares and banks an aliquot of the sputum specimens.…”
Section: Central Laboratory Proceduresmentioning
confidence: 99%
“…Multiple slides ofeach sputum specimen were stained separately to minimize the effect of staining variability. A complete description ofthe staining protocol used in this study can be found in previous reports (7,8). Briefly, slides were washed in phosphate-buffered saline (PBS), 0.01 M at pH 7.4, and incubated with SCLC or NSCLC antibodies in a sealed, humidified chamber at room temperature (25°C).…”
Section: Cytomorphology and Immunostaining Of Sputum Cellsmentioning
confidence: 99%